IbM Pemanfaatan Tanaman Eceng Gondok (Eichornia crassipes) untuk Kerajinan Tas - Asep Samsudin; Hendra Husnussalam (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Water hyacinth (Eichornia crassipes) is floating aquatic plant that reproduces very fast so it is assumed to damage aquatic environment. Other negative assumptions about the plant are that it can cause the flood. Fortunately, there is now a partner, PKBM (Center of Adult Education Activities) Alkaromah in Cililin, Bandung who has already utilized the plants to be bag craft. However, there are several obstacles faced by the partner. The problems are the lack of practical management of bags manufacture made from water hyacinth; started the process of revocation, drying, selection, splitting and weaving. The impractical management also leads to the results of work that are too time-consuming so it is late in answering market demands. Based on the situation, we as the Executive Team of IbM has assisted the Partner to make pressing machine to facilitate the utilization of water hyacinth to be bag craft. The IbM implementation aims to improve the quality of business management and expedite the process of drying and weaving water hyacinth by saving much time. Consequently, the pressing machine has produced significant impacts; the process of drying and weaving hyacinth no longer takes a long time and the results show the quality improvement. To increase the maximum benefit, the Executive Team and Partner also discuss the market share of products. Other efforts are also discussed to make the patent rights to obtain legal protection from the government. This is the preventive step to avoid others from conducting work recognition.